Lippincott's clinical skills series safety and mobility set - Conaway, Deborah Jean; Studio Three Productions (Philadelphia: Lippincott- Raven, 1997)
This video series offers essential guidence and detailed, up-close demontrations of clinical skills used by nurses and other health care providers
j.1-Applying protective devices; j.2-Using principles of body mechanics; j.3-Ensuring infection control
Videocassettes is available at Koleksi Media Perpustakaan HUKM
Technical consultant, Deborah Jean Conaway
Keywords: Biomechanics -- videocassettes; Infection Control -- videocassettes; Nursing Assessment -- videocassettes; Restraint, Physical -- videocassettes